Implementasi Kepemimpinan Demokratis Kepala Sekolah dalam Membangun Budaya Mutu dan Daya Saing Sekolah di SMA Brawijaya Smart School Malang - Minanda, Amiga Putri (Program Studi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Maulana Malik Ibrahim Malang, 2023)
The principal is a leader who has an important role in improving the quality and competitiveness of schools. Principals must have a serious attitude and high work ethic so that they can produce mature strategies. The strategy aims to make change truly materialized by the birth of new innovations that have an impact on improving the quality and competitiveness of education in schools. Democratic leadership style is a leadership style in which the leader involves all subordinates in making policies and actions. The purpose of this study was to determine and describe 1) the planning of the implementation of democratic leadership by the principal in building a culture of quality and school competitiveness at SMA Brawijaya Smart School Malang, 2) the implementation of the democratic leadership of the principal in building a culture of quality and school competitiveness at SMA Brawijaya Smart. School Malang, 3) the results of the planning of the implementation of the Principal's Democratic Leadership in Building a Culture of Quality and School Competitiveness at SMA Brawijaya Smart School Malang. The results showed that the implementation of the Principal's Democratic Leadership in Building a Culture of Quality and School Competitiveness at Sma Brawijaya Smart School Malang, namely 1) planning by making superior programs that are guided by the vision, mission and goals of the school in order to create a culture of quality and school competitiveness. which is SMART (Spiritual, Motivated, Active, Respectfull, Technological), 2) its implementation is in the form of student activities in the field of student affairs and academics that are accommodated by the school, 3) the result is the realization of a quality culture and school competitiveness as evidenced by behavior and achievements obtained by students.